Size Increase in Panum's Fusional Range Is Driven by Eccentricity and Not Separation. (September 2019) - Harrold, Ashleigh L.; Grove, Philip M.
Previous research has demonstrated that Panum's fusional range increases in the periphery, and this increase is usually attributed to eccentricity. However, it is unclear whether the increase in the periphery is driven by eccentricity or separation between the stimulus and the central fixation marker. In Experiment 1, we independently measured the effects of eccentricity and stimulus separation on Panum's fusional range for horizontal disparities. We observed significant increases in Panum's range as eccentricity increased independently of stimulus separation. Experiment 2 revealed that the extent of Panum's fusional range for vertical disparities increased with eccentricity independently of stimulus separation. Taken together, these results strongly support previously held conclusions that Panum's fusional range for both horizontal and vertical disparities increases with increasing eccentricity and is little impacted by stimulus separation.